Parental Involvement and English Language Teaching to Young Learners: Parentsâ Experience in Aceh - Wati, Shafrida (Sebelas Maret University, 2016)
The interest of teaching English to young learners increased rapidly since the language has significant influence in the modern world. English is strongly associated with social and economic power in globalizationâs context. Introducing English earlier offers opportunities to awaken the learnersâ enthusiasm and curiosity about the language, to achieve native-like accent, and to enable them to learn the language easily at further levels. However, there are controversies, particularly, about the age to start learning a new language. In Indonesia, English roles as a foreign language and the government have set up the policy to introduce English to students at elementary school. In order to support the language learning, parent involvement is extremely important to help the children learn and acquire the language. This study explores parentsâ perspectives toward English language teaching to young learners and further looks at their involvement in supporting their children learning the foreign language at home. An in-depth interview was conducted to parents with different educational backgrounds, professions, incomes, and gender groups in Langsa, Aceh province, Indonesia. Result revealed that parents have very positive attitude towards the language teaching to young learners. They enthusiastically support their children by helping them doing assignments, memorizing the vocabulary, providing learning medias such as English books, vocabulary pictures, English cartoonâs films, puzzles, and asking teachers the topic they do not understand from their childrenâs textbook. Lower education and lower income parents showed more enthusiasm in supporting their children.